(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Childhood seizures are a common reason for paediatric admission, and the severity of presentation often guides treatment intensity and prognostic counselling. Hospital profiles from Indian tertiary centres remain limited. Objective: To describe the clinical profile of paediatric admissions with seizures and to identify antenatal, perinatal, and clinical factors that distinguish children with a seizure disorder from those with a complex febrile seizure. Materials and Methods: A retrospective hospital-based analytical study was conducted at a tertiary care hospital over 24 months. Children aged 1 month to 18 years admitted with a confirmed seizure episode were included. Seizure was classified into seizure disorder and complex febrile seizure as per ILAE criteria. Fisher’s exact and Mann-Whitney U tests were used to compare groups; crude odds ratios with 95% confidence intervals were calculated. Results: Forty-three children were studied (mean age 5.1 ± 3.1 years; 60.5% male; 48.8% rural). Seizure disorder accounted for 55.8% (n=24) and complex febrile seizure for 44.2% (n=19). Status epilepticus occurred in 23.3%, ICU admission in 34.9%, and 44.2% required two or more antiepileptic drugs. Abnormal electroencephalography was present in 60.5% and abnormal neuroimaging in 34.9%. Pre-seizure developmental delay (crude OR 111, 95% CI 5.83–2112, p<0.001) and a history of birth asphyxia (OR 10.8, 95% CI 1.22–95.2, p=0.026) were strongly associated with seizure disorder rather than complex febrile seizure. Conversely, a febrile presentation (OR 0.08, 95% CI 0.01–0.45, p=0.002) and an age at first seizure under two years (OR 0.03, 95% CI <0.01–0.52, p=0.001) pointed toward complex febrile seizure. Conclusion. In this hospital cohort, seizure disorder accounted for the majority of admissions. Pre-seizure developmental delay, birth asphyxia, and an afebrile presentation favoured a diagnosis of seizure disorder over complex febrile seizure. Simple bedside features can support early differentiation and direct triage, investigation, and parental counselling.